2016
DOI: 10.1128/aac.02929-15
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Genotype 1 to 6 Protease Inhibitor Escape Variants: In Vitro Selection, Fitness, and Resistance Patterns in the Context of the Infectious Viral Life Cycle

Abstract: bHepatitis C virus (HCV) NS3 protease inhibitors (PIs) are important components of novel HCV therapy regimens. Studies of PI resistance initially focused on genotype 1. Therefore, knowledge about the determinants of PI resistance for the highly prevalent genotypes 2 to 6 remains limited. Using Huh7.5 cell culture-infectious HCV recombinants with genotype 1 to 6 NS3 protease, we identified protease positions 54, 155, and 156 as hot spots for the selection of resistance substitutions under treatment with the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 88 publications
3
20
0
Order By: Relevance
“…Our data thus highlight the potent antiviral efficacy of this drug that has been approved in combination with the NS5A inhibitor elbasvir for the treatment of genotype 1-infected patients. Previously published studies on the use of grazoprevir in vitro also support the notion that grazoprevir shows a uniquely high efficiency against different virus isolates (26,52,53).…”
Section: Con1supporting
confidence: 55%
See 3 more Smart Citations
“…Our data thus highlight the potent antiviral efficacy of this drug that has been approved in combination with the NS5A inhibitor elbasvir for the treatment of genotype 1-infected patients. Previously published studies on the use of grazoprevir in vitro also support the notion that grazoprevir shows a uniquely high efficiency against different virus isolates (26,52,53).…”
Section: Con1supporting
confidence: 55%
“…Importantly, treatment with a grazoprevir-elbasvir combination regimen has achieved high SVR rates in genotype 1-infected patients (51). However, so far for genotype 1b, protease inhibitor efficacy and resistance could not be evaluated in the context of the complete viral life cycle, due to the lack of infectious viruses comprising a genotype 1b-specific NS3/4A protease region (19,26,52,53). The genotype 1b C5A cultures developed in this study and previous full-length infectious systems for genotype 1a (43,44) permitted us to evaluate the efficacy of NS3/4A-protease and NS5A inhibitors against genotype 1 in the context of the complete viral life cycle.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Basic studies in infectious cell culture systems have shown great variation in their potency against different HCV variants and genotypes, and in their pattern of resistance [137,[219][220][221]; since they all target the protease active site substitutions conferring cross-resistance have been identified [12].…”
Section: Cyclophilin Inhibitors Against Hcvmentioning
confidence: 99%